Bipyridyl cobalt complex mediators in dye-sensitized solar cells - Scott, Michael J., author; Elliott, C. Michael, advisor (Colorado State University. Libraries, 2008)
Dye-sensitization of semiconductor substrates allows for efficient charge injection into the semiconductor conduction band. Dye-sensitized solar cells (DSSCs) exploit this for conversion of light into electrical energy. By employing mesoporous TiO2 a significant portion of visible light can be absorbed. The mesoporous TiO2, deposited on a transparent conducting oxide (TCO) medium, constitutes the photoanode of the DSSC. A wide range of materials may be used as a cathode. A redox electrolyte solution completes the cell. Typically, the I-/I3- redox couple has been employed in DSSCs. The use of bipyridyl cobalt complexes allows for tuning of the cell's electrochemistry, exploration of diverse cathode materials, and investigation of mediator solution additives. Cobalt complexes with alkyl, ester, and amide functionalities were considered throughout this body of work. The cobalt complexes were investigated on the basis of time dependence and electrode dependence. The cobalt complexes are stable for at least a period of one week when dissolved in γ-butyrolactone. Gold, carbon and modified TCO cathodes perform well in cells employing the alkyl substituted complex. Gold cathodes alone provide the best performance with cells employing the ester and amide substituted complex. An optically transparent cathode was developed for use in stacked DSSCs, allowing light that is not absorbed by the first DSSC in a stack to be absorbed by a second cell. A spectrally complementary dye in the second cell extends the light absorption to longer wavelengths. Spatial current images were obtained to investigate the local current behavior of cobalt mediated cells. Intentional electrode damage was visualized, and the effects of increased pressure on the cell were discussed. The use of phenothiazine (PTZ) moieties as co-mediators in cobalt mediated DSSCs was investigated. An anionic PTZ salt was most effective at reducing the photo-oxidized sensitizing dye. This PTZ salt enhanced the performance of DSSCs employing the alkyl substituted cobalt complex. Poor electronic coupling and decreased driving force prevents the PTZ salt from enhancing the performance of DSSCs employing the cobalt complexes with withdrawing functionalities.
Keywords: cobalt; cobalt complex; dye-sensitized solar cells; redox mediator; renewable energy; solar cells; solar energy; analytical chemistry; physical chemistry; energy